Does Second Language Learning Promote Neuroplasticity in Aging? A Systematic Review of Cognitive and Neuroimaging Studies - Ware, Caitlin; Dautricourt, Sophie; Gonneaud, Julie; Chételat, Gael (Frontiers in Aging Neuroscience, 2021)
As the population ages, understanding how to maintain older adults’ cognitive abilities is essential. Bilingualism has been linked to higher cognitive reserve, better performance in executive control, changes in brain structure and function relative to monolinguals, and delay in dementia onset. Learning a second language thus seems a promising avenue for cognitive enhancement in older adults. Our review aims to determine whether learning a foreign language in later life improves cognition and promotes neuroplasticity. We screened articles from the Pubmed, Scopus, and Science Direct databases to identify interventional studies using second language training in senior participants, including either cognition or neuroimaging as outcome measures. A total of nine articles were found, with only one neuroimaging study. Results from these studies are inconsistent but tend to suggest that second language learning is associated with improvement in attentional switching, inhibition, working memory, and increased functional connectivity. We discuss the implication of these results, and suggest new directions and methodological recommendations for future research.